2019
DOI: 10.1016/j.aott.2019.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and knowledge skill levels of orthopedic surgeons about radiation safety and fluoroscopy use: A survey analysis

Abstract: ObjectiveThe aim of this study was to evaluate the behaviour and knowledge skill levels of Turkish orthopedic surgeons about fluoroscopy usage and radiation safety.MethodsThe questionnaire, consisting of nineteen questions, was sent to orthopaedic surgeons and requested by a total of 323 surgeons online. The questions were about personal information, training and behaviours related to radiation and fluoroscopy usage, and the use of protective equipment.ResultsA total of 277 individuals completed the questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 11 publications
5
28
0
10
Order By: Relevance
“…This higher number in the level of knowledge component could also be attributed to the fact that this being an online survey could provide an opportunity for the participants to not be completely honest while filling up of forms and take use of the internet in finding the correct answer. Similar results were seen in other studies by Papendorp et al, Fidan et al and Tuncer et al [4][5][6] On finding the socio-demographic characteristics of the study population, mean ± S.D age of the study population was found to be 42 ± 16.8 years. Majority, 148 (98.6%) of the study participants were males, whereas only 2 (1.4%) were female respondents.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This higher number in the level of knowledge component could also be attributed to the fact that this being an online survey could provide an opportunity for the participants to not be completely honest while filling up of forms and take use of the internet in finding the correct answer. Similar results were seen in other studies by Papendorp et al, Fidan et al and Tuncer et al [4][5][6] On finding the socio-demographic characteristics of the study population, mean ± S.D age of the study population was found to be 42 ± 16.8 years. Majority, 148 (98.6%) of the study participants were males, whereas only 2 (1.4%) were female respondents.…”
Section: Discussionsupporting
confidence: 91%
“…A few study on awareness and practices of occupational exposure were found internationally but none in India. [4][5][6] Only study was found, which was conducted in India by Mahajan et al but its objective to analyse the amount of radiation received by orthopaedic surgeons in India using standard precautionary measures and also to bring awareness about the use of image intensifier safety in everyday practice. 1 Therefore, our study, though conducted among 150 orthopaedic surgeons, through an online survey was the only one of its kind.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Também é indicado que os princípios de proteção radiológica não são respeitados durante a realização de exames por cirurgiões ortopédicos. Foi constatado ainda que os médicos, independente do título, não implementam as medidas adequadas para reduzir a exposição à radiação ionizante (9) . O conhecimento sobre os princípios de proteção radiológico e sobre o uso da radiação ionizante no processo de trabalho em saúde também foi considerado deficitário entre enfermeiros (10)(11) .…”
Section: Introductionunclassified